Dynamics and group identity among Lima’s gamers, the case of competitiveness in the League of Legends video game - Toykin Minaya, Francis Irineo (2020)
The aim is to seek to understand the cultural aspects  that emerge through group dynamics from the consumption of video games in Lima. Qualitative research was conducted on the social imaginary and practices of gamers  from the ANG and SHOT teams of the League of Legends  video game, within the local competitive environment.  Fieldwork was conducted at the World Cyber Games 2013  Festival-Peru, involving observation and participation in  video game booths and related spaces. What is the group  identity of these players? The answer involves analysis of  cultural variables such as identification, game, performance, territoriality, consumption, distinction and masculinity,  in the two representative spaces: the virtual, as a stage  where the players are transfigured into characters; and the  physical, in which they act as players, through interaction  and the use of technological devices. They are «virtual urban tribes», sharing values and interests, whose sense  of belonging is based on affective, emotional and competitives.